Theory of Planned Behavior, Information Technology, and Taxpayer Compliance - Sigit Hermawan; Tri Yuda Lesmana; Duwi Rahayu; Nihlatul Qudus Sukma Nirwana; Ruci Arizanda Rahayu (Jurnal Bisnis dan Akuntansi, 2021)
This research aims to analyze the influence Theory of Planned Behavior which proxy with attitude, Theory of Planned Behavior which proxy with subjective norm, Theory of Planned Behavior which proxy with perceived behavioral control, information technology, and taxpayer awareness against tax compliance. This research used quantitative as the research methodology and the data used is primary data. The object of this research is the individual taxpayers conducting business registered in KPP”X” Sidoarjo East Java, Indonesia. The population in this study amounted to 7.207 and the sampling technique used simple random sampling with a total of 100 respondents. Partially, the yield of the research stated that the Theory of Planned Behavior which proxy with attitude, Theory of Planned Behavior which proxy with subjective norm, information technology, and taxpayer awareness influence on tax compliance, while the Theory of Planned Behavior which proxy with perceived behavioral control is not influence on tax compliance. Simultaneously, the yield of the research stated that the Theory of Planned Behavior which proxy with attitude, Theory of Planned Behavior which proxy with subjective norm, Theory of Planned Behavior which proxy with perceived behavioral control, information technology, and taxpayer awareness influence on tax compliance.